LASP: Fast global potential energy surface exploration - Huang, Si‐Da; Shang, Cheng; Kang, Pei‐Lin; Zhang, Xiao‐Jie; Liu, Zhi‐Pan (Wiley interdisciplinary reviews. Computational molecular science, 2019)
Here we introduce the LASP code, which is designed for large‐scale atomistic simulation of complex materials with neural network (NN) potential. The software architecture and functionalities of LASP will be overviewed. LASP features with the global neural network (G‐NN) potential that is generated by learning the first principles dataset of global PES from stochastic surface walking (SSW) global optimization. The combination of the SSW method with global NN potential facilitates greatly the PES exploration for a wide range of complex materials. Not limited to SSW‐NN global optimization, the software implements standard interfaces to dock with other energy/force evaluation packages and can also perform common tasks for computing PES properties, such as single‐ended and double‐ended transition state search, the molecular dynamics simulation with and without restraints. A few examples are given to illustrate the efficiency and capabilities of LASP code. Our ongoing efforts for code developing and G‐NN potential library building are also presented. This article is categorized under: Software > Simulation Methods LASP is an atomistic simulation package targeted for solving the complex PES problems using the global neural network potentials.